Gambaran Kualitas Air pada Depot Air Minum Isi Ulang di Kelurahan Tarus - Febriyanti Donata Peso Ndoka; Marylin Susanti Junias; Yuliana Radja Riwu (Yayasan Literasi Sains Indonesia, 2024)
Water is one of the absolute needs required by all living things, especially humans. The quality of refill water into drinking water in bulk from and sell directly to consumers. The quality of refill water that can be consumed is that has gone through a processing process startingfrom raw water which is pumped using a jet pump while being injected into the reactor tank, then pumped into a filter tube, to the disinfection process using ultraviolet. The purpose of this study was to determine the quality of refill drinking water in Tarus Vilage based on microbiological and chemical variable. The type of research used is descriptive methods. The population in this study were 5 depots. The data obtained will be analyzed according to the 2010 minister of health regulation on drinking water quality. The results of laboratory examinations of Escherichia coli parameters showed that the raw water quality was good in depots 2, 3, 4 and 5, while depot 1 had passed the threshold of 2 mg/L, which means it did not meet the requirements. Good quality drinking water is depot 1, 2, 3, 4, and 5. Based on the chloride and nitrite parameters, the results obtained are good quality raw water and drinking water are depot 1, 2, 3, 4, and 5. Required periodic checks by Public Health Center staff on water quality at 5 refill drinking water depots so that each depot has the latest license.